2018
DOI: 10.15294/lc.v12i2.14178
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Native Students’ Motivation in Learning English at STIE Perbanas Surabaya

Abstract: Low competence in English for the students of Non English native speakers has been crucial so far for the teachers in language teaching in Indonesia. This study attempts to explore students ‗motivation in learning English at STIE Perbanas Surabaya. This is a qualitative research and a case study. This study analyzed the data by means of a descriptive analysis. This method was chosen to describe the qualitative data taken from the students at STIE Perbanas Surabaya who were taking English subject. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…The students are motivated because of personal goals, interest, self-confidence and their self-efficacy. This finding were agreed upon the previous research conducted by Budiana & Djuwari, (2018); the result showed that there are two types of motivations owned by the students in learning English; intrinsic and intrinsic motivation.…”
Section: Discussionsupporting
confidence: 92%
“…The students are motivated because of personal goals, interest, self-confidence and their self-efficacy. This finding were agreed upon the previous research conducted by Budiana & Djuwari, (2018); the result showed that there are two types of motivations owned by the students in learning English; intrinsic and intrinsic motivation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, students need to increase or maintain their motivation to attain the goal. Motivation plays a crucial aspect in the learning process (Rofi, Rukmini, & Hartono, 2014;Budiana & Djuwari, 2018). Motivation is believed as one of the paramount factors in attaining a goal.…”
Section: Introductionmentioning
confidence: 99%
“…Since high motivation results in high-quality learning and creativity, it is especially important to find the factors and forces that can make the teachers motivated (Ryan & Deci, 2000) Scientific papers are often called scientific writing. In this case, scientific writing tends also be compared to non-scientific writing (Budiana & Djuwari, 2018). Brotowidjoyo (2007) stated that "scientific writing is essay science that presents facts and is written according to methodology good and correct writing."…”
Section: Frameworkmentioning
confidence: 99%
“…It is realized in the annual activity plan of each school in the form of KBK program (Competency-Based Curriculum) and character education. This can, in turn, induce motivation in the classroom (Budiana & Djuwari, 2018). Character education itself includes six programs, namely environmental improvement, improvement of character classrooms, building relationships among students, between teachers, teachers and students, teachers and other school residents.…”
Section: Introductionmentioning
confidence: 99%